Spaces of Communication: Elements of Semio-Pragmatics - Odin, Roger (Film Theory in Media History, 2022)
"Semio-pragmatics, an approach to the study of film and audiovisual media first proposed by Roger Odin in the early 1980s, shifted the focus from textual analysis to the interaction of text and context and to the institutional modes of framing and reading which shape the viewer’s engagement with the film. A response to an impasse in post-1968 film semiotics and psychoanalytical approaches to film spectatorship, semio-pragmatics contributed significantly to the further development of film studies alongside Cultural Studies, neo-formalism, historical reception studies and the phenomenology of film. Spaces of Communication offers a concise introduction to semio-pragmatics and condenses the intellectual trajectory of one of the foundational figures of film studies into a relatively short and accessible volume. It is a book which testifies to the author’s deep and rich intellectual engagement with a vast array of objects ranging from the classics of"